Etika Pelayanan Publik Di Kantor Kelurahan Tamaona Kecamatan Tombolo Pao Kabupaten Gowa - Akbar, A Muh Alwilah; Mappamiring, Mappamiring; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine the ethics of public service at the Office of Tamaona Village, Buttono Pao District, Gowa Regency. This study used qualitative research, data sources used primary and secondary, the number of informants was 6 people. Data collection used observation techniques, interviews and documentation, data analysis techniques using data reduction steps, data presentation, verification of data that were qualitative, as well as using the validation of triangulation data that was triangulation of sources, techniques, and time. The results showed that the ethics of public service applied at the Tamaona Office, Tombolo Pao Subdistrict, Gowa Regency, had been implemented well, if viewed from the aspect of 1) Equality of rights had run well, serving the community regardless of race, ethnicity, religion and politics 2) Justice, serving the community kindly, giving explanations during the service process, serving the community, all the people were treated equally. 3) Loyalty, especially honorarium employees were still loyal to the institution regardless of how much salary they had received and even worked for years. 4) Responsibility, not yet fully done well.Keywords: Public Service Ethics, Village